Conditioning (1997)
Exercise scientists have identified nine elements that comprise the definition of fitness. The following lists each of the nine elements and an example of how they are used:- Strength - the extent to which muscles can exert force by contracting against resistance (holding or restraining an object or person) Power - the ability to exert maximum muscular contraction instantly in an explosive burst of movements (lumping or sprint starting) Agility - the ability to perform a series of explosive power movements in rapid succession in opposing directions (ZigZag running or cutting movements) Balance - the ability to control the body's position, either stationary (e.g. a handstand) or while moving (e.g. a gymnastics stunt) Flexibility - the ability to achieve an extended range of motion without being impeded by excess tissue, i.e. fat or muscle (Executing a leg split) Local Muscle Endurance - a single muscle's ability to perform sustained work (Rowing or cycling) Cardiovascular Endurance - the heart's ability to deliver blood to working muscles and their ability to use it (Running long distances) Strength Endurance - a muscle's ability to perform a maximum contracture time after time (Continuous explosive rebounding through an entire basketball game) Co-ordination - the ability to integrate the above listed components so that effective movements are achieved.